Lead, headline, news abstract? – genre conventions of news sections on newspaper websites - Tereszkiewicz, Anna (Studia Linguistica Universitatis Iagellonicae Cracoviensis, 2012)
Increasing popularity and dynamic expansion of online newspapers creates a need for an in-depth analysis of online press, genre and discourse properties of online news in particular. The aim of the following analysis is to investigate genre characteristics of a newly developed news structure – a news abstract. The analysis examines the basic conventions concerning the purpose, form and content of these text types. The study encompasses news abstracts published on the websites of leading British, German and Polish newspapers. The inclusion of websites of culturally distinct newspapers was designed to evaluate the degree of universality and internationalization of the structure.